The Spatial Distribution of Poverty in Vietnam and the Potential for Targeting - Baulch, Bob (The World Bank, 2002)
Minot and Baulch combine household survey and census data to construct a provincial poverty map of Vietnam and evaluate the accuracy of geographically targeted antipoverty programs. First, they estimate per capita expenditure as a function of selected household and geographic characteristics using the 1998 Vietnam Living Standards Survey. Next, they combine the results with data on the same household characteristics from the 1999 census to estimate the incidence of poverty in each province. The results show that rural poverty is concentrated in 10 provinces in the Northern Uplands, 2 provinces in the Central Highlands, and 2 provinces in the Central Coast. The authors use Receiver Operating Characteristics curves to evaluate the effectiveness of geographic targeting. The results show that the existing poor communes system excludes large numbers of poor people, but there is potential for sharpening poverty targeting using a small number of easy-to-measure household characteristics. This paper is a joint product of Macroeconomics and Growth, Development Research Group, and the International Food Policy Research Institute. The authors may be contacted at n.minot@cgiar.org or b.baulch@lds.ac.uk